THE ENGLISH LANGUAGE ANXIETY OF UNIVERSITY STUDENTS IN AN INTERNATIONAL PROGRAM: A CASE STUDY OF THAI AND NON-THAI STUDENTS IN THE ENGLISH FOR BUSINESS COMMUNICATION PROGRAM AT DHURAKIJ PUNDIT UNIVERSITY - Kulwattanapaisarn, Patummawadee; Yiamsawat, Thananchai; Siripitrakool, Prapapan; Soe, Win Naing (Journal of Liberal Art of Rajamangala University of Technology Suvarnabhumi, 2022)
This study aimed to examine 1) the level of English language anxiety of students in an international program 2) to investigate the relationship between the students’ learning achievement and their level of English language anxiety, and 3) to analyze the differences in the sources of English language anxiety between Thai students and non-Thai students. The samples were taken from 36 university students studying in English for Business Communication (International Program) in the Faculty of Arts. The instrument used in this study was adopted from a questionnaire from a study of foreign language learning anxiety developed by Paranuwat (2011). The data was analyzed using descriptive statistics and the Pearson’s product moment correlation coefficient. The research results were found as follows: 1) students had moderate anxiety with the average mean of 2.84 and the two major sources of students’ English language learning anxiety when considering the six components of performance anxiety were fear of being less competent than others, with the mean of 3.31 and test anxiety with the mean of 3.00 2) there was a significant negative correlation between English language learning anxiety and the moderate-achieving group of students, and 3) the distinct differences in the sources of English language learning anxiety according to the six components of performance anxiety of Thai and non-Thai students were fear of being less competent than others and test anxiety with a mean of 3.52 and 2.87, and test anxiety with a mean of 3.15 and 2.87, respectively.